A hard Act to follow? The evolution and performance of UK climate governance. (20th October 2021) - Lockwood, Matthew
ABSTRACT: This article provides an analysis of the origins and effects of UK climate governance. It is centrally concerned with the relationships between politics and climate institutions, both in how political conditions have shaped the emergence of climate governance, and in how the resulting institutions subsequently structure climate politics. The analysis brings out three key themes. First, a focus on the CCA can overlook the enduring importance of the parallel climate governance architecture provided by the European Union. Second, it is important to see UK climate governance within a wider political and institutional context, as these results of this context, especially tensions between ambition and instability, have influenced its evolution. Third, this design, and other aspects of the evolution of UK climate governance framework, have in turn had implications for the strengths and weaknesses of the framework and how it has met key governance challenges.